The cost of conformity: masking among neurodivergent workers and the relationship with mental health and job attitudes - Clancy, Rebecca L., author; Fisher, Gwenith, advisor; Dik, Bryan, committee member; Nelson, Niccole, committee member; Henle, Christine, committee member (Colorado State University. Libraries, 2025)
Neurodivergent individuals are an important, but underrepresented, part of the workforce who face a number of challenges when it comes to obtaining and maintaining employment. Masking, defined here as the strategies used to conceal neurodivergent traits in an effort to conform to neurotypical norms, has been shown to have negative repercussions for individuals' well-being, but has limited empirical research tied to the workplace. Using self-determination theory, the present study investigated how masking is related to worker mental health and job attitudes. Self-determination theory, and more specifically, basic psychological needs theory, has been used to explain motivation and well-being through the satisfaction of three basic needs: autonomy, competence, and relatedness. In this study, I hypothesized that masking would be associated with negative consequences for workers at least in part due to the active frustration of these needs, such that the experience of masking actively thwarts basic needs for autonomy, competence, and relatedness, and is likely associated with lower satisfaction of these needs as well. N=293 neurodivergent participants completed an online survey regarding their masking behaviors, perceptions of basic psychological needs, well-being, and job attitudes. Data were analyzed using higher-order structural equation modeling to test the hypothesized models regarding the associations between masking, needs frustration, need satisfaction, and individual mental health and job attitudes and found initial evidence for the role of need frustration and need satisfaction as atemporal and partial mediators between masking, mental health, and job attitudes. These results may inform future research and theory regarding the psychological process of masking used by a variety of neurodivergent individuals and its presence in the workplace. Results may also be used to inform HR policy and training programs to better support neurodivergent workers and increase broader understanding and knowledge for neurotypical leaders, managers, and coworkers.